THE STATE FINANCIAL MECHANISMS OF HIGHER EDUCATION OBTAINING FACILITATION OF THE USA - Ivanitska, Olga; Red’ko, Serhiy; Panchenko, Alla (Continuing Professional Education: Theory and Practice, 2019)
In the article experience of the USA is analysed in regards of different financial instruments application to facilitate the access to obtain higher education. Certainly, that the extension of tax credit is selected as a basic instrument. The basics are outlined near the state assistance to obtain the higher education, namely: the special legislation is accepted and the special institutes are determined; the wide arsenal of instruments and their options is used; wide differentiation of terms of programs realization is allowed in the states; there is combination of work experience of financial institutions and educational establishments; the permanent revision of the mode of realization of the programs comes true, as a rule, to get the best satisfaction of interests and necessities of consumer of educational services.It is determined the models of providing financial facilitated access to education in the developed countries of North America and Europe (the use of state credit facility assist in funding higher education; state guarantees for loans when the state is the guarantor of the loan and / or interest payments; providing state tax credits; grants training; initiating programs funded with state guarantee compensation in case of bankruptcy of a financial institution). The necessity of observance of such principles for Ukraine was underlined: to adopt specific legislation; to outline the special powers involved institutions; to permit broad differentiation conditions the implementation of programs in the regions; to combine of professional experience in financial institutions and educational institutions; to provide constant viewing options implementation of programs; to respect the principle of transparency and providing full information understandable.